Optical quantum communications: an experimental approach - Pinto, Armando N.
Quantum laws can be used to implement secure communication channels; this has been named quantum cryptography. In quantum cryptography the security does not depend of limited computational power, but is inherent to the laws that govern the propagation and detection of single and entangled photons. We show how single and entangled photon-pairs can be efficiently generated using four-wave mixing in optical fibers. We analyze the source statistics, degree of entanglement and impact of spontaneous Raman scattering. By coding information in the photons polarization we are able to transmit quantum information over 20 km of standard single mode fiber.